The relationship between HMGB1 and autophagy in the pathogenesis of diabetes and its complications - Yang, Kun; Cao, Feng; Wang, Weili; Tian, Zhenyu; Yang, Lu (Frontiers in Endocrinology, 2023)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels and has become the third leading threat to human health after cancer and cardiovascular disease. Recent studies have shown that autophagy is closely associated with diabetes. Under normal physiological conditions, autophagy promotes cellular homeostasis, reduces damage to healthy tissues and has bidirectional effects on regulating diabetes. However, under pathological conditions, sustained and excessive autophagy activation leads to cell death and may contribute to the progression of diabetes. Therefore, restoring normal autophagy may be a key strategy to treat diabetes. High-mobility group box 1 protein (HMGB1) is a chromatin protein that is mainly present in the nucleus and can be actively secreted or passively released from necrotic, apoptotic, and inflammatory cells. HMGB1 can induce autophagy by activating various pathways. Studies have shown that HMGB1 plays an important role in insulin resistance and diabetes. In this review, we will introduce the biological and structural characteristics of HMGB1 and summarize the existing knowledge on the relationship between HMGB1, autophagy, diabetes, and diabetic complications. We will also summarize potential therapeutic strategies that may be useful for the prevention and treatment of diabetes and its complications.